Menuju Kajian Sejarah Lembaga Peradilan Shari'ah di Kawasan Asia Tenggara: Sebuah Kajian Metodologi Sejarah Perbandingan Kawasan - Adiwidjajanto, Koes (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2012)
This article does not take a historical approach to Islamic Jurisprudence per se but rather presents real historical data that reconstructs the application of Islamic laws in Southeast Asia. It highlights significant aspects of how Islamic laws influenced various regions within the area. Scholars agree that Islam, as a major global religion, has become a central identity in the Indonesian Archipelago, among the Malay in the Peninsular region, and within the Chams community in southern Indochina. It has also been a basis for distinct identity in the southern Philippines and the Pattani region. This article examines the historical application of Sharī‘ah law among local inhabitants and its significant role alongside ‘adat laws (customs) among the Muslim Malays and Indonesians. Western influence, starting in the late sixteenth century, contributed to the establishment of a Muhammadan Law court, which evolved into the Sharī‘ah court in the independent states. This article aims to serve as a preliminary study for a comparative history of Southeast Asia, focusing on topics such as the development and reorganization of the Muhammadan Law court.